Moderating role of meaningful interaction on the relationship between participation of diversity engagement activities and campus climate with civic responsibility - Loh, Yit Phing (2020)
Due to changing demographics in higher education and increasing demands of the educative value of diversity in need, "twenty-first-century college student diversity outcomes" is a term used to describe the skills necessary for college graduates to function in the diverse world. University level is an excellent platform to cultivate diversity engagement among undergraduate students. There are many studies suggested that through diversity engagement, it will enhance various learning outcome, including a sense of civic responsibility. This study analyzes the relationship between the level of participation in curricular diversity engagement activity, co-curricular diversityengagement activity, level of campus climate, level of participation in meaningful interaction with a sense of civic responsibility. Finally, it tested the level of meaningful interaction as a moderator between the relationship of level of participation in curricular, co-curricular and civic responsibility among students of different ethnicities at six Malaysia universities. By adopting purposive sampling, 1420 respondents were involved in this study. Survey through self-administered questionnaires was used in this study. Social Package for the Social Sciences (SPSS) and Structured Equation Modelling (SEM) with Partial Least Squares (PLS)was used to test the relationship between constructs in this study. The study found that less than 25 per cent of students have a high level of participation in curricular and co-curricular diversity engagement activity. More than 80 per cent of students agreed that a sense of civic responsibility is importantto them. This study also found that co-curricular diversity engagement activity, campus climate and meaningful interaction have significant relationship with civic responsibility. However, curricular diversity engagement activity did not have relationship with civic responsibility. Meaningful interaction did not moderate the relationship between co-curricular diversity engagement activities with civic responsibility. However, it did moderate the relationship between curricular diversity engagement activities with civic responsibility. The findings provided useful information to better understanding regarding the level of participation of students in diversity engagement activity and their sense of civic responsibility. This finding also could be used by the university to develop better curricular and co-curricular diversity engagement activity and enhance campus climate that supports diversity.